LOCALS’ PERSPECTIVES ON TOURISM DEVELOPMENT AT RURAL AND URBAN LEVEL - Avcı, Ceren; Özgen Çiğdemli, Aslı Özge (My University, 2022)
The perception of the locals respecting the impacts of tourism can be determined by the factors such as how the community, which they are member of is, affected by tourism; how tourism affects social activities and the attitudes of political and administrative authorities towards tourism. The main purpose of this study is to estimate whether locals’ negative perceptions (NP) and positive perceptions (PP), locals’ support for tourism development (STD) and community participation (CP) differ at rural and urban levels. The sub-aims are to figure out whether there is any mediation effect and correlations among NP, PP, STD and CP. Data were obtained from Muğla (urban) and Fethiye (rural) through face-to-face surveys with a total number of 400 participants. Confirmatory factor analysis (CFA), validity and reliability analysis and path analysis for Fethiye and Muğla have performed. No statistically significant effect of CP, PP and NP on STD was found in Muğla and Fethiye. In Fethiye locals’ PP have a significant and positive effect on STD. Locals’ PP and NP have a significant and positive effect on CP. Consequently, a difference has found between Fethiye and Muğla concerning the impact of positive and negative perceptions on the participation in the tourism processes.
Keywords: Otelcilik; Konaklama; Spor ve Turizm; Kamu Yönetimi; Sosyoloji; İktisat